Varsity's soldiers : the University of Toronto Contingent of the Canadian Officers Training Corps, 1914-1968 - McGeer, Eric (Canadian experience of war., 2019)
"The role of Canadian universities in selecting and training officers for the armed forces is an important yet overlooked chapter in the history of higher education in Canada. For more than fifty years, the University of Toronto supported the largest and most active contingent of the Canadian Officers Training Corps (COTC), which sent thousands of officer candidates into the regular and reserve forces. Based on the rich fund of documents housed in the university archives, Varsity's Soldiers offers the first full-length history of military training in Toronto. Beginning with the formation of a student rifle company in 1861, and focussing on the story of the COTC from 1914 to 1968, author Eric McGeer seeks to enlarge appreciation of the university's remarkable contribution to the defence of Canada, the place of military education in an academic setting, and the experience of the students who embodied the ideal of service to alma mater and to country."--